Concrete based on multi-element composite super-fluid cementing material system

By adopting a multi-component superfluidic gelling material system in steel pipe arch rib concrete and optimizing the mix ratio design, the limitations of traditional concrete in terms of strength, durability and construction performance are solved, and concrete with high strength, high durability and good construction performance is achieved.

CN119797836APending Publication Date: 2025-04-11NANJING TECH UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411869868.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The traditional steel pipe arch rib concrete mix design has limitations in strength, durability and construction performance. How to determine the optimal mineral blending amount and ensure construction performance has become a challenge.

Method used

Concrete based on a multi-component superfluidic gelling material system is adopted, and the dosage and proportion of various raw materials are accurately calculated, and the mix ratio design is optimized to improve the strength, durability and working performance of concrete.

Benefits of technology

By optimizing the chemical components and particle grading of composite cementitious materials, it reduces hydration heat, reduces cracking, improves compactness and durability, and meets the needs of high-performance concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797836A_ABST
    Figure CN119797836A_ABST
Patent Text Reader

Abstract

The invention relates to concrete based on a multi-element composite superfluid cementing material system. The concrete is prepared from the following raw material components in parts by mass: 535 to 550 parts of a cementing material, 715 to 720 parts of fine aggregate, 980 to 990 parts of coarse aggregate, 6.4 to 6.6 parts of a water reducing agent and 165 to 175 parts of water, the weight ratio of the water to the gel material is 0.31 to 0.32; the cementing material is prepared by compounding the following components in percentage by mass: 45-50% of cement, 15-30% of fly ash, 10-25% of mineral powder, 4-6% of silica fume and 5-10% of an expanding agent. By optimizing the chemical components of the composite cementing material, the hydration reaction of the cementing material is promoted to be performed in stages, the hydration heat is reduced, the concrete cracking is reduced, and the alkali content in the concrete is reduced; by optimizing the grain composition and appearance of the composite cementing material, the physical effect of the cementing material is boosted to be maximized, and the working performance and compactness of the concrete are improved; the expansion agent is doped to compensate hydration shrinkage of the concrete, so that the performance of the cementing material is improved, and a technical support is provided for preparing high-performance concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of concrete, in particular to concrete based on a multi-component composite superfluid cementitious material system. Background Art

[0002] In the field of bridge and construction engineering, steel tube arch structures are widely used due to their high bearing capacity and convenient construction. As an important load-bearing part of the bridge, the design of the concrete mix ratio of the steel tube arch rib is directly related to the bearing capacity, durability and construction efficiency of the bridge. The traditional steel tube arch rib concrete mix ratio design often uses a single cementitious material, such as ordinary Portland cement. Although this mix ratio design can meet certain construction requirements, it has limitations in terms of strength, durability, and working performance.

[0003] In recent years, with the continuous development of concrete technology, multi-component composite cementitious materials have been more and more widely used in concrete mix design. Multi-component composite cementitious materials can effectively reduce the hydration heat of concrete, reduce cracking, and improve the strength and durability of concrete by adding active mineral admixtures such as fly ash, mineral powder, and silica fume. Mineral admixtures such as fly ash, mineral powder, and silica fume, when mixed with cement in a certain proportion, can achieve a certain balance in chemical composition and particle grading, taking advantage of each other's strengths and making up for each other's weaknesses, thereby improving the physical and chemical properties of concrete.

[0004] In the mix design of steel tube arch rib concrete, the use of multi-component composite cementitious materials can not only improve the strength and durability of concrete, but also improve the working performance of concrete and reduce the difficulty of construction. However, the application of multi-component composite cementitious materials also brings new challenges, such as how to determine the optimal dosage of various mineral admixtures, how to ensure the construction performance and working performance of concrete, etc. Therefore, it is necessary to conduct in-depth research on the application of multi-component composite cementitious materials in the mix design of steel tube arch rib concrete to optimize the performance of concrete and improve the bearing capacity and durability of bridges. Summary of the invention

[0005] In order to overcome the above-mentioned problems existing in the prior art, the purpose of the present invention is to provide a concrete based on a multi-component composite superfluid cementitious material system. This technology adopts multi-component composite cementitious materials and optimizes the mix design of concrete by accurately calculating the dosage and proportion of various raw materials to improve the strength, durability and working performance of the concrete.

[0006] The specific technical solutions provided by the present invention are as follows:

[0007] A concrete based on a multi-component composite superfluid cementitious material system, comprising the following raw material components in parts by weight: 535-550 parts of gel material, 715-720 parts of fine aggregate, 980-990 parts of coarse aggregate, 6.4-6.6 parts of water reducer, and 165-175 parts of water; the weight ratio of water to gel material is 0.31-0.32;

[0008] The cementitious material is prepared by mixing the following components in percentage by weight: 45-50% cement, 15-30% fly ash, 10-25% mineral powder, 4-6% silica fume and 5-10% expansion agent.

[0009] Preferably, the chemical components in the cementitious material include SiO2, CaO and Al2O3, the molar ratio of SiO2:CaO is 1:0.9-1.3, and the molar ratio of SiO2:Al2O3 is 2.5-4:1.

[0010] Preferably, the cement is silicate cement with a strength grade of 52.5, an average particle size of 3 to 45 μm, and a specific surface area of ​​330 to 360 m 2 / kg, apparent density 3.08-3.16g / cm 3 , SiO2 molar content > 20%, CaO molar content > 62%, Al2O3 molar content > 6%.

[0011] Preferably, the fly ash is of grade I, with a loss on ignition of less than 5%, an average particle size of 1 to 30 μm, and a specific surface area of ​​450 to 550 m 2 / kg, apparent density 2.50g / cm 3 , SiO2 molar content > 52%, CaO molar content > 6%, Al2O3 molar content > 21%.

[0012] Preferably, the mineral powder is of S95 grade, with an average particle size of 1.5 to 40 μm and a specific surface area of ​​420 to 460 m 2 / kg, apparent density 2.97g / cm 3 , SiO2 molar content > 36%, CaO molar content > 39%, Al2O3 molar content > 11%.

[0013] Preferably, the silica fume has a loss on ignition of less than 4.0%, an average particle size of 0.16 to 0.32 μm, and a specific surface area of ​​18,000 to 22,000 m 2 / kg, apparent density 2.37g / cm 3 , SiO2 molar content>94%, CaO molar content>0.2%, Al2O3 molar content>0.3%.

[0014] Preferably, the fine aggregate is river sand with a fineness modulus of 2.8, a mud content ≤3.0%, and a mud block content ≤1.0%; the coarse aggregate includes 5-10mm crushed stone and 10-20mm crushed stone, and the crushed stone blending ratio is 20%:80% of 5-10mm crushed stone:10-20mm crushed stone.

[0015] Preferably, the water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate reaches 25%-30%.

[0016] Preferably, the raw material components include the following parts by weight: 539 parts of gel material, 716 parts of fine aggregate, 984 parts of coarse aggregate, 6.5 parts of water reducer, and 161.6 parts of water; the weight ratio of water to gel material is 0.31;

[0017] The cementitious material is compounded with the following components in percentage by weight: 49% cement, 25% fly ash, 15% mineral powder, 5% silica fume and 6% expansion agent.

[0018] Preferably, the slump of the concrete before pouring is controlled to be 230-250mm, the expansion is controlled to be 650-750mm, the compressive strength of the concrete is 7d≥43.9MPa, 28d≥58.2MPa, 56d≥67.1MPa; the water absorption rate is ≤2.6%, the electric flux is ≤445C, and the water seepage height is ≤9.4mm.

[0019] The concrete based on the multi-component composite superfluid cementitious material system of the present invention has the following beneficial effects:

[0020] 1. By optimizing the chemical composition of composite cementitious materials, the hydration reaction of cementitious materials is promoted to proceed in stages, which reduces the hydration heat, reduces concrete cracking, and reduces the alkali content in concrete; by optimizing the particle grading and appearance of composite cementitious materials, the physical effect of cementitious materials is maximized, and the working performance and density of concrete are improved;

[0021] The addition of expansive agents can compensate for the hydration shrinkage of concrete, thereby improving the performance of cementitious materials and providing technical support for the preparation of high-performance concrete.

[0022] 2. Among composite cementitious materials, cement particles have the largest particle size, followed by ground slag powder and fly ash, and silica fume has the smallest particle size. During the hydration process of composite cementitious materials, powder material particles of different particle sizes fill each other, reducing the gaps between particles, thereby further reducing the total porosity of the composite cementitious materials after coagulation and hardening, and improving the compactness of concrete.

[0023] 3. Mineral powder particles are irregular and have a rough surface, which will reduce the fluidity of fresh concrete; fly ash particles have a smooth surface and are spherical and glassy, ​​which can improve the fluidity of fresh concrete; silica fume particles are spherical and glassy with the smallest particle size and the largest specific surface area, and their water demand is large, which will reduce the fluidity of fresh concrete; the combination of mineral powder, fly ash, silica fume and cement has a certain plasticizing and water-reducing effect, which is beneficial to the formation of a dense concrete structure.

[0024] 4. Fly ash has fine particles, large specific surface area, and contains active components, which can react with Ca(OH)2 in water to form dense hydration products. Increasing the amount of fly ash added can increase the strength and durability of concrete.

[0025] Slag powder has high activity and can react with Ca(OH)2 in water to produce cementitious substances, which promotes the hydration and hardening process of concrete. In self-compacting concrete, the addition of slag powder can effectively fill the internal voids of concrete, improve the density and durability of concrete, and improve the mechanical properties and chemical stability of concrete.

[0026] Silica fume has high reactivity and fineness, and can fully react with water-phase calcium lime to form cementitious materials, accelerate the hydration and hardening process, and improve the strength and durability of concrete. Adding silica fume can slow down the hydration rate of cement, extend its service life, and improve the impermeability and frost resistance of concrete, making it more suitable for use in harsh environments and improving its durability and reliability.

[0027] Fine aggregates such as fly ash, slag powder, and silica fume can fill concrete pores, reduce permeability, and improve self-compacting properties. The active ingredients in these admixtures can react with Ca(OH)2 in water to form cementitious substances, further strengthening the concrete structure and improving its compressive strength. Selecting the right amount of admixtures can slow down the speed of the hydration reaction inside the concrete and extend the service life of the concrete. Therefore, the compounding of multi-component cementitious powder materials can not only achieve multiple hydration reactions, but also play a role in morphological complementarity and gradation optimization, thereby improving the compactness and durability of the concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is the particle morphology of each powder material in the composite gelling material;

[0029] Figure 2 This is the cement particle size distribution diagram;

[0030] Figure 3 This is the particle size distribution diagram of the mineral powder;

[0031] Figure 4 This is the fly ash particle size distribution diagram;

[0032] Figure 5This is the particle grading diagram of silica fume;

[0033] Figure 6 is the compressive strength curve;

[0034] Figure 7 This is the relationship between the aggregate mixing ratio and the void ratio. DETAILED DESCRIPTION

[0035] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation method, structure, characteristics and effects of the present invention are described in detail below in combination with the preferred embodiments.

[0036] Example 1

[0037] This embodiment provides a concrete based on a multi-component composite superfluid cementitious material system, comprising the following raw material components by weight: 539 parts of gel material, 716 parts of fine aggregate, 984 parts of coarse aggregate, 6.5 parts of water reducer, and 161.6 parts of water; the weight ratio of water to gel material is 0.31;

[0038] The cementitious material is compounded with the following components in percentage by weight: 49% cement, 25% fly ash, 15% mineral powder, 5% silica fume and 6% expansion agent.

[0039] The chemical components of the cementitious material include SiO2, CaO and Al2O3, the molar ratio of SiO2:CaO is 1:0.9-1.3, and the molar ratio of SiO2:Al2O3 is 2.5-4:1

[0040] The cement is P.O52.5 cement, with an average particle size of 3-45μm and a specific surface area of ​​344m 2 / kg, apparent density 3.16g / cm 3 , its alkali content is <0.6%, 80μm sieve residue is <2.0%, and 45μm sieve residue is <4.0%.

[0041] The fly ash is Grade I, with a loss on ignition of <5%, an average particle size of 1-30 μm, and a specific surface area of ​​510 m 2 / kg, apparent density 2.50g / cm 3 , 7d compressive strength activity index>80%, 28d compressive strength activity index>90%.

[0042] The mineral powder is S95 grade, with a mass coefficient K>1.3, an average particle size of 1.5-40μm, and a specific surface area of ​​445m 2 / kg, apparent density 2.97g / cm 3 , 7d compressive strength activity index>95%, 28d compressive strength activity index>105%.

[0043] Silica fume ignition loss <4.0%, average particle size 0.16-0.32μm, specific surface area 18000m 2 / kg, apparent density 2.37g / cm 3 , 28d compressive strength activity index>90%.

[0044] The specific surface area of ​​the expansion agent is 305m 2 / kg, apparent density 2.70g / cm 3 .

[0045] The fine aggregate is river sand with a fineness modulus of 2.8, a mud content ≤3.0%, and a mud block content ≤1.0%; the coarse aggregate includes 5-10mm crushed stone and 10-20mm crushed stone, and the crushed stone mixing ratio is 20%:80% of 5-10mm crushed stone: 10-20mm crushed stone. The needle-like particle content of the coarse aggregate is ≤8%, the mud content is ≤1.0%, and the mud block content is ≤0.5%.

[0046] The water reducer is a polycarboxylic acid-based slow-setting high-performance water reducer with a water reduction rate of 28% and a solid content of 16.6%.

[0047] The chemical composition and proportion of each powder material in the composite cementitious material were analyzed by X-ray diffraction method. The analysis results are shown in Table 1.

[0048] Table 1 Chemical components and proportions of various powder materials of composite cementitious materials (%)

[0049]

[0050] The calcium oxide content in cement is the highest, at 62.50%, followed by the silicon dioxide content, at 20.03%; silica fume is rich in silicon dioxide, at a content of up to 94.79%; mineral powder contains the highest calcium oxide, at 39.47%, followed by silicon dioxide content, at 36.61%, which is equivalent to the calcium oxide content, and then aluminum oxide content, at 11.79%; fly ash contains a relatively high silicon dioxide content, at 52.86%, followed by aluminum oxide content, at 21.30%, while the calcium oxide content is very low, at only 6.01%. Among all the chemical components of cementitious materials, calcium oxide, silicon dioxide and aluminum oxide have a greater influence on the physical and chemical properties of cementitious materials. The above three mineral admixtures are mixed with cement in a certain proportion to achieve a certain balance in chemical composition, thereby improving the performance of cementitious materials.

[0051] The particle size distribution, particle size and morphology of each powder material in the composite cementitious material were analyzed by microscopic experiments using a laser particle size analyzer, a particle size distribution analyzer and a microscope. The analysis results are shown in Table 2 and Figure 1 As shown, Figure 1Among them, (a) is cement, (b) is mineral powder, (c) is fly ash, and (d) is silica fume.

[0052] Table 2 Particle size analysis results of cementitious powder materials

[0053]

[0054] As shown in Table 2, in the composite cementitious materials, cement particles have the largest particle size, followed by ground slag powder and fly ash, and silica fume has the smallest particle size. The various powder materials in the cementitious materials are blended in proportion to form a good continuous micro-gradation. During the hydration process of the composite cementitious materials, the powder material particles of different particle sizes fill each other, reducing the gaps between the particles, thereby further reducing the total porosity of the composite cementitious materials after coagulation and hardening, and improving the compactness of the concrete.

[0055] The particle morphology of mineral admixtures has different degrees of influence on the performance of concrete. Figure 1 It can be seen that mineral powder particles are irregular and have a rough surface, which will reduce the fluidity of fresh concrete; fly ash particles have a smooth surface and are spherical and glassy, ​​which can improve the fluidity of fresh concrete; silica fume particles are spherical and glassy with the smallest particle size and the largest specific surface area, and their water demand is large, which will reduce the fluidity of fresh concrete. Therefore, the compounding of mineral powder, fly ash, silica fume and cement has a certain plasticizing and water-reducing effect, which is beneficial to the formation of a dense structure of concrete.

[0056] From Table 2 and Figure 2-5 It can be seen that the particle size of cement powder is mostly between 3 and 45μm. The particle distribution and particle size of cement powder have a direct impact on the cement hydration process. Cement particles with a particle size of 3 to 32μm play a major role in strength. The 3 to 10μm part has high early strength, and the 10 to 32μm part has high later strength.

[0057] The more 3-40μm particles there are and the higher the particle sphericity, the better the cement performance;

[0058] The particle size of fly ash is between 1 and 30 μm. The activity of fly ash is proportional to the content of particles smaller than 10 μm and inversely proportional to the content of particles larger than 45 μm. The content of particles between 10 and 20 μm has the greatest impact on cement strength, and particles larger than 30 μm are negatively correlated with cement strength. Therefore, to improve the strength of cement, the content of fly ash particles smaller than 30 μm should be increased as much as possible, the content of particles larger than 45 μm should be reduced, and the content of particles between 30 and 45 μm should be limited;

[0059] The particle size of mineral powder is between 1.5 and 40 μm. When the cement particles are coarser, mineral powder particles with a size less than 10 μm have a positive effect on the fluidity of mortar, among which the correlation of 10 to 20 μm is the greatest; when the cement particles are finer, mineral powder particles with a size less than 40 μm have a positive effect on the fluidity of mortar, among which the correlation of 20 to 40 μm is the greatest.

[0060] The particle size of silica fume is between 0.16 and 0.32 μm. The particles of silica fume are very fine, and are shaped like glass spheres under a microscope. They are non-crystalline and amorphous, and have excellent physical and chemical properties. Silica fume added to cement clinker can be fully dispersed and filled in the gaps between cement particles, making the slurry more compact. It has a strong absorption capacity for Ca(OH)2 generated after cement hydration, forming a well-developed calcium silicate gel, which greatly improves the strength of concrete.

[0061] Hydration mechanism of powder materials:

[0062] Fly ash is a common mineral admixture produced during the coal combustion process in thermal power plants. Its main components are silicon oxide, aluminum oxide, iron oxide, etc. Fly ash has fine particles, large specific surface area, and contains active components that can react with Ca(OH)2 in water to form dense hydration products. Therefore, increasing the amount of fly ash added can improve the strength and durability of concrete.

[0063] The main components of slag powder include iron oxide, silicon oxide, aluminum oxide, etc. Slag powder has high activity and can react with Ca(OH)2 in water to produce cementitious substances, which promotes the hydration and hardening process of concrete. In self-compacting concrete, the addition of slag powder can effectively fill the internal voids of concrete, improve the density and durability of concrete, and improve the mechanical properties and chemical stability of concrete.

[0064] Silica fume is a commonly used inorganic mineral admixture that has a great influence on the performance of self-compacting concrete. First, silica fume has high reactivity and fineness, and can fully react with water-phase calcium lime to form a cementitious material, accelerating the hydration and hardening process. This process can improve the strength and durability of concrete. Secondly, the addition of silica fume can slow down the hydration rate of cement and extend its service life. In addition, silica fume can also improve the impermeability and frost resistance of concrete, making it more suitable for use in harsh environments and improving its durability and reliability.

[0065] Fine aggregates such as fly ash, slag powder, and silica fume can fill concrete pores, reduce permeability, and improve self-compacting properties. The active ingredients in these admixtures can react with calcium hydroxide in water to form cementitious substances, further strengthening the concrete structure and improving its compressive strength. Selecting the right amount of admixtures can slow down the speed of the hydration reaction inside the concrete and extend the service life of the concrete. Therefore, the compounding of multi-component cementitious powder materials can not only achieve multiple hydration reactions, but also play a role in morphological complementarity and gradation optimization, thereby improving the compactness and durability of the concrete.

[0066] Therefore, this embodiment adopts multi-component composite cementitious materials, and then optimizes the mix design of concrete by accurately calculating the amount and proportion of various raw materials, which can improve the strength, durability and working performance of concrete. The mix design steps are as follows.

[0067] A concrete mix design procedure based on a multi-component composite superfluid cementitious material system

[0068] 1. Determine the test strength

[0069] According to the "Ordinary Concrete Mix Design Code" (JGJ55-2011), the concrete trial strength is determined according to the following formula: f cu.o ≥f cu.k +1.645σ, σ is 6.0MPa.

[0070] f cu.o ≥f cu.k +1.645σ=55+1.645×6.0=64.9MPa

[0071] 2. Determine the volume and mass of coarse aggregate

[0072] According to the Technical Specification for Application of Self-compacting Concrete (JGJT283-2012), the filling index of self-compacting concrete can be obtained by looking up the table of SF1, and the volume of coarse aggregate per cubic meter of concrete is Vg, which is 0.32~0.35m 3 , take 0.35m 3 The apparent density of coarse aggregate is 2810kg / m 3 , so the mass of coarse aggregate is:

[0073] m g =V g ·ρ g =0.35×2810=984kg.

[0074] 3. Determine the mortar volume

[0075] V m =1-V g =1-0.35=0.65m 3

[0076] 4. Determine the volume fraction of sand

[0077] According to the "Technical Specification for Application of Self-compacting Concrete" (JGJT283-2012), the volume fraction of sand in mortar is Φ s Take 0.42~0.45, and take the value as 0.42.

[0078] 5. Determine the volume and mass of sand

[0079] Volume of sand V s =V m ·Φ s =0.65×0.42=0.27m 3 The apparent density of sand is 2650kg / m 3 , the mass of sand m s =V s ·ρ s =0.27×2650=716kg, so the sand rate is

[0080] 6. Determine the slurry volume

[0081] V p =V m -V s =0.65-0.27=0.38m 3

[0082] 7. Determine the apparent density of cementitious materials

[0083] The apparent density of cement is 3160kg / m 3 The apparent density of fly ash is 2500kg / m 3 The apparent density of slag powder is 2970kg / m3, the apparent density of silica fume is 2370kg / m3, the apparent density of expansion agent is 2700kg / m3, the fly ash content is 25%, the slag powder content is 15%, the silica fume content is 5%, the expansion agent content is 6%, and the apparent density of cementitious material is calculated as follows:

[0084]

[0085] 8. Determine the water-cement ratio

[0086] The compressive strength of cement ce =1.1×52.5=57.8MPa, the gelling coefficient γ1 of fly ash is 0.4, the gelling coefficient γ2 of slag powder is 0.9, the gelling coefficients γ3 and γ4 of silica fume and expansion agent are both 1.0, and the water-binder ratio is calculated as follows:

[0087]

[0088] 9. Determine the quality of cementitious materials

[0089] According to the provisions of the specification "Concrete Quality Control Standard" (GB50164-2011), according to Table 3.1.9, the air content of concrete is less than or equal to 5.5%, take 2.5%, the gas volume V a =25L; apparent density of water ρ w 1000kg / m 3 , so the mass of cementitious material is:

[0090]

[0091] 10. Determine the quality of water used

[0092] The quality of water used m w =m b ·(m w / m b )=539×0.31=167kg.

[0093] 11. Determine the quality of cement and mineral admixtures

[0094] Fly ash mass m1 = 539 × 0.25 = 135 kg, slag powder mass m2 = 539 × 0.15 = 81 kg, silica fume mass m3 = 539 × 0.05 = 27 kg, expansion agent mass m4 = 539 × 0.06 = 32 kg, cement mass m c =m b -m1-m2-m3-m4=539-135-81-27-32=264kg.

[0095] 12. Determine the quality of admixtures

[0096] The admixture dosage α is 1.2%, and the admixture mass m ca =m b α=539×0.012=6.5kg, water content of water reducing agent: 6.5×(1-16.6%)=5.4kg / m 3 , actual water consumption ratio: 167-5.4=161.6kg / m 3 .

[0097] Determine the initial mix ratio as:

[0098] Cement: fly ash: slag powder: silica fume: sand: crushed stone: water reducer: expansion agent: water = 264: 135: 81: 27: 716: 984: 6.5: 32: 161.6 (kg / m 3 ), the theoretical apparent density of concrete is: 2407.1kg / m 3 .

[0099] Before pouring concrete, the slump is controlled at 230-250mm, and the expansion is controlled at 650-750mm. After testing, the compressive strength of concrete is 43.9MPa at 7d, 58.2MPa at 28d, and 67.1MPa at 56d; the water absorption rate is 2.6%, the electric flux is 445C, and the water seepage height is 9.4mm.

[0100] Comparative Example 1

[0101] In order to determine the optimal water-binder ratio, comparative example 1 was set up, and the concrete benchmark mix ratio and material consumption are shown in Table 3.

[0102] Table 3 Concrete benchmark mix ratio and material consumption (kg / m 3 )

[0103]

[0104]

[0105] The 56d compressive strength curve of concrete under each water-binder ratio condition is as follows Figure 6 As shown in the figure. When the water-binder ratio is 0.31, the concrete strength is 7.7% higher than the design strength value. Considering the workability and economy of concrete comprehensively, 0.31 is selected as the optimal water-binder ratio.

[0106] Comparative Example 2

[0107] The coarse aggregate includes 5-10 mm crushed stone and 10-20 mm crushed stone. In order to determine the optimal mixing ratio of the two groups of particle sizes, comparative example 2 is set to study the relationship between different mixing ratios and void ratios and determine the optimal ratio.

[0108] The results are shown in Table 4 and Figure 7 As shown, when the mixing ratio of 5-10 mm crushed stone and 10-20 mm crushed stone is 20:80, the void ratio is the lowest, which is 37.4%. Therefore, 20:80 is selected as the optimal mixing ratio.

[0109] Table 4 Relationship between the mixing ratio of coarse aggregate and void ratio

[0110]

[0111] Comparative Example 3

[0112] This comparative example adopts the existing concrete formula, and compares this comparative example with the concrete of Example 1. The concrete formula and material dosage are shown in Table 5.

[0113] Table 5 Concrete formula and material dosage (kg / m 3 )

[0114]

[0115] The working performance of the concrete of this comparative example is compared with that of the concrete of Example 1. The indicators of the working performance test of the self-compacting concrete include: workability, slump, T50 expansion, J-ring expansion, L-type instrument test, air content, etc. The test results of the concrete working performance are shown in Table 6. From the test results in Table 6, it can be seen that the concrete of Example 1 of the present invention has better working performance than the concrete of the prior art, meets the requirements of on-site back pressure injection, and although the air content is slightly higher, it does not exceed 5%, which is conducive to maintaining the state of superplastic concrete.

[0116] Table 6 Comparison of concrete working performance

[0117]

[0118] The concrete of this comparative example and Example 1 were subjected to compressive strength and density tests, wherein the compressive strength includes the strength at the ages of 7d, 28d and 56d, and the density includes three indicators: electrical flux, water absorption rate and water seepage height at 56d. The comparison of the test results is shown in Table 7.

[0119] Table 7 Comparison of concrete strength and compactness

[0120]

[0121] From the test results in Table 7, it can be seen that by adding a variety of mineral admixtures to concrete, the later strength of concrete can be significantly improved, and the strengthening effect is better than that of single mineral admixtures, but the early concrete strength is low. The improvement of concrete density by compound mineral admixtures is better than single admixtures. The water absorption and electric flux of concrete after compounding with mineral powder, fly ash and silica fume are lower than the various density indicators of concrete with single fly ash. There is a correlation between the water absorption and electric flux of concrete. When the water absorption of concrete is low, the corresponding electric flux value is also low. When the water absorption of concrete is high, the electric flux value also increases. This shows that these two indicators can well reflect the density of concrete. The water seepage height of concrete with multiple additions of mineral admixtures is significantly lower than that of concrete with single addition of fly ash. It can be seen that the multiple additions of mineral admixtures in concrete can improve the density of concrete. This is due to the micro-aggregate effect of mineral admixtures, which improves the pore size and distribution characteristics of concrete, forming a large number of unconnected fine pores that block the diffusion path of water, thereby improving the impermeability of concrete.

[0122] The present invention also calculates the concrete cost, as shown in Table 8. The concrete cost per cubic meter in the embodiment of the present invention can save 14.77 yuan. Although silica fume is added to the optimized concrete, the steel tube concrete only needs to meet the requirement of no volume shrinkage after hardening, and the amount of expansion agent is reduced, so the total cost is reduced. Therefore, this preparation technology truly achieves the goal of cost reduction and efficiency improvement, energy conservation and emission reduction, and is a green, economical and durable technical approach that is worthy of promotion and application in engineering.

[0123] Table 8 Concrete cost accounting (yuan / m 3 )

[0124]

[0125] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A concrete based on a multi-component composite superfluid cementitious material system, characterized in that: The raw material components include the following parts by weight: 535-550 parts of gel material, 715-720 parts of fine aggregate, 980-990 parts of coarse aggregate, 6.4-6.6 parts of water reducing agent, and 165-175 parts of water; The weight ratio of water to gel material is 0.31-0.32; The cementitious material is prepared by mixing the following components in percentage by weight: 45-50% cement, 15-30% fly ash, 10-25% mineral powder, 4-6% silica fume and 5-10% expansion agent.

2. The concrete based on the multi-component composite superfluid cementitious material system according to claim 1 is characterized in that: The chemical components in the cementitious material include SiO2, CaO and Al2O3, the molar ratio of SiO2:CaO is 1:0.9-1.3, and the molar ratio of SiO2:Al2O3 is 2.5-4:

1.

3. The concrete based on multi-component composite superfluid cementitious material system according to claim 2 is characterized in that: The cement is silicate cement with a strength grade of 52.5, an average particle size of 3 to 45 μm, and a specific surface area of ​​330 to 360 m 2 / kg, apparent density 3.08-3.16g / cm 3 , SiO2 molar content > 20%, CaO molar content > 62%, Al2O3 molar content > 6%.

4. The concrete based on the multi-component composite superfluid cementitious material system according to claim 2 is characterized in that: The fly ash is Grade I, with a loss on ignition of <5%, an average particle size of 1 to 30 μm, and a specific surface area of ​​450 to 550 m 2 / kg, apparent density 2.50g / cm 3 , SiO2 molar content > 52%, CaO molar content > 6%, Al2O3 molar content > 21%.

5. The concrete based on multi-component composite superfluid cementitious material system according to claim 2, characterized in that: The mineral powder is S95 grade, with an average particle size of 1.5-40 μm and a specific surface area of ​​420-460 m 2 / kg, apparent density 2.97g / cm 3 , SiO2 molar content > 36%, CaO molar content > 39%, Al2O3 molar content > 11%.

6. The concrete based on multi-component composite superfluid cementitious material system according to claim 2, characterized in that: Silica fume ignition loss <4.0%, average particle size 0.16 ~ 0.32μm, specific surface area 18000 ~ 22000m 2 / kg, apparent density 2.37g / cm 3 , SiO2 molar content>94%, CaO molar content>0.2%, Al2O3 molar content>0.3%.

7. The concrete based on multi-component composite superfluid cementitious material system according to claim 1, characterized in that: The fine aggregate is river sand with a fineness modulus of 2.8, a mud content of ≤3.0%, and a mud block content of ≤1.0%; the coarse aggregate includes 5-10mm crushed stone and 10-20mm crushed stone, and the crushed stone mixing ratio is 20%:80% for 5-10mm crushed stone and 10-20mm crushed stone.

8. The concrete based on multi-component composite superfluid cementitious material system according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate reaches 25%-30%.

9. The concrete based on multi-component composite superfluid cementitious material system according to claim 1, characterized in that: The raw material components include the following parts by weight: 539 parts of gel material, 716 parts of fine aggregate, 984 parts of coarse aggregate, 6.5 parts of water reducing agent, and 161.6 parts of water; The weight ratio of water to gel material is 0.31; The cementitious material is compounded with the following components in percentage by weight: 49% cement, 25% fly ash, 15% mineral powder, 5% silica fume and 6% expansion agent.

10. The concrete based on multi-component composite superfluid cementitious material system according to claim 9, characterized in that: The slump of the concrete before pouring is controlled to be 230-250mm, the expansion is controlled to be 650-750mm, the concrete compressive strength is 7d≥43.9MPa, 28d≥58.2MPa, 56d≥67.1MPa; the water absorption rate is ≤2.6%, the electric flux is ≤445C, and the water seepage height is ≤9.4mm.